ALAT PENGEMBANGAN KOGNITIF MENGGUNAKAN MEDIA KANCING BAJU PADA ANAK - Hurmawati, Rida; Aziz, Reza Dzikrotul Maula; Mardiani, Reni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2025)
Preschool is an educational level before primary education aimed at children from birth to six years old, providing educational stimulation to support their physical and cognitive development, ensuring readiness for further education through formal, non-formal, and informal channels. The researcher observed that at RA Mutiara Bangsa Dolopo Madiun, there was a lack of cognitive development in children, as they often expressed frustration, said